Designing Amino Functionalized Titanium-Organic Framework on Separators Toward Sieving and Redistribution of Polysulfides in Lithium-Sulfur Batteries - Kang, Xiaoya; He, Tianqi; Dang, Hao; Li, Xiangye; Wang, Yumeng; Zhu, Fuliang; Ran, Fen (Nano-Micro Letters, 2025)
Shuttle effect of polysulfides overshadows the superiorities of lithium–sulfur batteries. Size–sieving effect could address this thorny trouble rely on size differ in polysulfides and lithium ions. However, clogged polysulfides pose some challenges for cathode and are rarely recycled during charging/discharging. Herein, an amino functionalized titanium-organic framework is designed for modifying lithium–sulfur batteries separator to address the aforementioned challenges. Wherein, the introduction of amino narrows titanium–organic framework pore size, enabling functional separator to selectively modulate lithium ions and polysulfides migration using size-sieving effect, thereby completely suppressing polysulfides shuttle. Furthermore, the blocked polysulfides will be adsorbed on the separator surface by positively charged amino leveraging electrostatic adsorption, ensuring polysulfides to redistribute and reuse, and boosting active materials utilization. Significantly, the migration of lithium ions is not hindered since there are lithium ions transfer channels formed via Lewis acid–base interaction with the help of amino. Combined with these virtues, the lithium–sulfur batteries with amino functionalized titanium-organic framework modified separator enjoy an ultralow attenuation rate of 0.045% per cycle over 1000 cycles at 1.0C. Electrostatic adsorption and Lewis acid–base interaction cover deficiencies existing in the inhibition of polysulfides shuttle by size-sieving effect, providing fresh insight into the advancement of lithium-sulfur batteries. Highlights: 1 Amino could narrow the sub-nanopore size of Ti–MOF modified layer to around 0.8 nm for perfectly inhibiting polysulfides shuttle. 2 Amino enables redistribution and reutilization of blocked polysulfides via leveraging electrostatic adsorption. 3 Electrostatic adsorption and Lewis acid–base interaction make up for the deficiency of size effect in inhibiting polysulfides shuttle.